Perbedaan Persepsi Antara Mahasiswa Senior Dan Junior Mengenai Profesi Akuntan Pada Program S-1 Reguler Fakultas Ekonomi Universitas Lancang Kuning - kamilah, faizah (Komunitas Manajemen Kompetitif, 2017)
This Research aimed to see whether there are differences in perception between senior and junior students of the accounting profession in the S-1 Regular program. The results showed that the S-1 Regular program, senior students perceptions of the